Contacts with environmental biodiversity affect human health: links revealed during the initial waves of the COVID-19 pandemic - Divín, Daniel; Toman, Jan; Flegr, Jaroslav; Vinkler, Michal (Scientific reports, 2024)
The gradual decrease in the prevalence of serious infectious diseases over the last century has been followed by increase in so called "modern" diseases, including allergies, chronic inflammatory conditions, psychiatric, and metabolic disorders. Between 2019 and 2022, public awareness of the threat of infectious diseases in humans was renewed by the global pandemic of a new type of a coronavirus, the SARS-COV-2. This public interest opened improved possibilities to test hypotheses on the factors associated with inter-individual variation in susceptibility to infectious and "modern" diseases. Based on the Hygiene hypothesis and Biodiversity hypothesis, we predicted that contacts with natural environment and wildlife in childhood and/or in adulthood can improve general health and decrease the risks of severe COVID-19 progression or prevalence of the "modern" diseases, namely the allergies. Here we report the results of an online, self-evaluating questionnaire survey conducted in the Czech Republic, where we contrasted selected health issues, and linked them to the living environment, including the level of contacts with biodiversity. In a sample of 1188 respondents, we revealed a significant association of time spent in nature or contacts with biodiversity with physical and mental health, or incidence of allergies. This is unlike the COVID-19 progression, which was related to age, physical health, smoking, allergies, and interaction of age with smoking, but not to contacts with the natural environmental diversity. Our findings regarding to physical and mental health and allergies are in agreement with the Biodiversity hypothesis of allergy and, linking human and environmental health, they urge for One Health approach application.
Keywords: Civilization diseases; Surveys and Questionnaires; pandemie; Humans; Allergies; lidé středního věku; Infectious diseases; alergie; duševní zdraví; Female; Aged; mladý dospělý; dospělí; Pandemics; Biodiversity antigen richness; Hypersensitivity; senioři; lidé; průzkumy a dotazníky; Adult; COVID-19; Wildlife; Contacts with nature; ženské pohlaví; biodiverzita; Male; Middle Aged; Czech Republic; Young Adult; Česká republika; mužské pohlaví; SARS-CoV-2; Mental Health; Biodiversity